Teachers’ Participation in Their Performance Appraisal in Delivery of Education in Mixed Day Secondary Schools in Uasin Gishu County, Kenya - Okemasisi , Kinikonda (African Journal of Education,Science and Technology (AJEST), 2014)
The main purpose of this paper was to make an assessment of and to determine the level of Teachers‟ involvement and participation in their Performance Appraisal Practices in mixed day public and private secondary schools in Uasin Gishu County-Kenya. The author used the cross sectional research design and naturalistic (phenomenological) designs to collect quantitative and qualitative information from the study participants. The sample size was 228 teachers, 21 school principals and 3 Quality Assurance and Standard Officers in the County. Simple random sampling and purposeful sampling were used. The questionnaires were used to collect data from the teachers while interview guides were used to collect data from the school principals and the DQASOs. The instruments for data collection were validated by peer review and the pilot study. Test-retest was used to establish the reliability of the instruments with the help of the SPSS using Statistical Package for Social Science (SPSS) version 17. The study found out that most of the teachers were not fully involved in the entire appraisal process. The benefits of involving the teachers would include; making them own the appraisal system, and discover weaknesses among others. Majority of the teachers perceived and rated the appraisal practices as not helpful towards their professional growth. Based on the findings, the study therefore recommended that principals diversify appraisal practices and increase the frequency in order to produce the desired results. There should also be full involvement of teachers in appraisal process. The Ministry of Education Science and Technology and the Teachers Service Commission should conduct a nationwide study and develop appropriate and effective appraisal tools to achieve the desired results